THE EMERGENCE OF LEGAL SYSTEM IN ISLAMIC FINANCE - Qonita, Nuha (Fakultas Syariah, 2018)
Legal system and jurisdiction take an important role in developing system or product innovation. The principle of Islamic financial transaction is recently elaborated in different frames of finance. It describes the challenge of Islamic finance in several countries which is linked with the perspective of stakeholders, consumer, industry, and the existing regulation. Various problems and recent decision making concept should be solved properly. This article aims to re-emphasize the rationality of Islamic finance regulation adjusted with consumer’s need. In some points, this study is used as the analysis on Islamic finance regulation. This is a study case categorized in qualitative research. The in-depth analysis is done on the basis of legal appeal in the court of Indonesia and is referred to Indonesian law about Islamic finance.